EFFECT OF ADDING VITAMINE-E AND FLAX OIL Linum usitatissimum TO THE DIETS OF TWO TYPES OF CARP FISH Cyprinus carpio L. , Hypophthalmichthys molitrix RAISED IN FLOATING CAGES OF UPHRATE RIVER – CITY OF SAMAWAH - & AL-AMARY, AL-KHAFA (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The study was conducted for a period 120 days of metal floating cages were used 2.25 × 2.25 × 1.5 m dimensions, for breeding two types of carp fish and common carp Cyprinus carpio.L and silver carp Hypophthalmichthys molitrix rate of 240 fish (120 common carp +120 Silver carp) for each treatment in three replications, and made laboratory four diets with obrocana content of between 27.83% and 28.52% and energy between 439.39 and 445.68 Kilusarh/100 g as it was the bush first free any addition treatment called the second control and treatment contained vitamin E (500 mg/kg) and third-treatment contained linseed oil by 1% and the treatment represented a fourth of all oil and vitamin mentioned the same proportions. The results of the statistical analysis significant preference (P ≤0.05) for the fourth treatment  that contained the flax oil, vitamin E in weight gain overall, reaching for each of the common and silver carp, common carp, silver carp 109.31 and 60.30 and 49.01 g / fish in a row , and in the daily increase since 0.910 and 0.502 0.408 g / fish / recorded consecutive day, and in the relative growth coefficient as 398.541% and 583.172% and 286.834%, respectively reached, and in qualitative growth 0.01330% and 0.01600% and 0.01127%, respectively, and the rate of 3.597 and 3.008 and 4.322 feed conversion, respectively.